Motivaciones gastronómicas del turista y satisfacción del servicio en restaurantes de gastronomía típica Iquitos 2021 - Icomedes Garcia, Allison Franceska (2022)
The present research study aimed to determine the relationship between the gastronomic motivations of the tourist and the satisfaction of the service in restaurants of typical gastronomy, of the city of Iquitos during the period, 2021. The type of study used was quantitative, the design non experimental, crosssectional and correlational; the sample constituted 120 tourists, who visited typical restaurants of the city of Iquitos. The instrument was a Likert Scale (de Carvache, et al 2017), whose validity was 87.80% and reliability 85.76%. It was possible to determine that of the 100% (120) of tourists, 52.5% (63) presented a medium level of motivation, 42.5% (51) high motivation level and 5.0% (6) low motivation level; 55.8% (67) said they were satisfied and 44.2% (53) dissatisfied. In the correlation of categories of gastronomic motivations: interpersonal, a r = 0.717 (p < 0.01), cultural a r = 0.667 (p < 0.01), sensoryhealthy a r = 0.661 (p < 0.01) and emotional a r = 0.402 (p < 0.01) . When relating both variables under study, it was determined that there is a significant statistical relationship (X2 = 40.471; p = 0.000 < 0.05) between gastronomic motivations and tourist satisfaction, when receiving the service in the restaurants of typical gastronomy, of Iquitos. The results obtained will contribute to promoting socioeconomic, cultural, environmental sustainability and therefore, preserve this intangible heritage, which generates greater opportunities for employment, economic growth and quality of service, among others.